Introdução à noção de sustentação - Aubert, Emmanuel de Saint (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2017)
We attempt to introduce the necessity, meaning and anthropological issues surrounding a new concept, “lift” [portance]. This thinking stems from both a clinical and philosophical background that explores the carnal (fleshly) foundation of desire. From a phenomenology in dialogue with psychology, psychoanalysis and philosophy of education, the concept of lift addresses the very foundations of our openness to the world and to others.